Here, there, & everywhere: Development and validation of a cross-culturally representative measure of subjective career success - Briscoe, Jon P.; Kaše, Robert; Dries, Nicky; Dysvik, Anders; Unite, Julie A.; Adeleye, Ifedapo; Andresen, Maike; Apospori, Eleni; Babalola, Olusegun; Bagdadli, Silvia; Çakmak-Otluoglu, K. Övgü; Casado, Tania; et al. (Elsevier, 2021)
Subjective career success continues to be a critical topic in careers scholarship due to ever changing organizational and societal contexts that make reliance upon external definitions of success untenable or undesirable. While various measures of subjective career success have been developed, there is no measure that is representative of multiple nations. In this study, we develop and validate a new subjective career success scale, which is unique from currently available measures in that it was developed and validated across a broad representation of national cultures. We validated the scale across four phases and several studies cumulatively involving 18,471 individual respondents from 30 countries based upon the GLOBE and Schwartz cultural clusters. This scale allows for addressing career success differences both within and across cultures. It is also easily applicable in everyday practice for companies operating in multi-country contexts. We explore theoretical and practical implications.
Keywords: Career success; Cross-cultural; Scale development; fi=Henkilöstöjohtaminen|en=Human Resource Management|